2017 29th International Teletraffic Congress (ITC 29) 2017
DOI: 10.23919/itc.2017.8064358
|View full text |Cite
|
Sign up to set email alerts
|

Providing Information Resilience Through Modularity-Based Caching in Perturbed Information-Centric Networks

Abstract: Abstract-In this paper, we investigate the provision of a new form of resilience, namely information resilience -targeting reliable communication of information under normal and adverse network conditions. We harness the power and flexibility of information-centric networking (ICN) paradigm where content are named and can be explicitly identified as opposed to the current host-centric Internet. Using ICN principles, a new modularity-based information caching approach is proposed that leverages the concept of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
3
0
3
Order By: Relevance
“…However, it only considers single-hop routing in its distributed caching system, and thus cannot be directly applied into the path routing with multi-hops. [43] employs a modularity-based information caching approach by leveraging information reachability to achieve reliable communication of information under adverse network conditions. [44] maximizes the expected caching gain through a distributed resilient caching algorithm (DR-Cache) considering network failures.…”
Section: Related Workmentioning
confidence: 99%
“…However, it only considers single-hop routing in its distributed caching system, and thus cannot be directly applied into the path routing with multi-hops. [43] employs a modularity-based information caching approach by leveraging information reachability to achieve reliable communication of information under adverse network conditions. [44] maximizes the expected caching gain through a distributed resilient caching algorithm (DR-Cache) considering network failures.…”
Section: Related Workmentioning
confidence: 99%
“…For information resilience, [10] considered implicit cooperation amongst caching nodes by exploiting features of network topology and proposed a modularity-based caching scheme that allows nodes within a community structure to cache content with origins outside of that community. This solution does not require explicit communication between caching nodes but nonetheless, still increases the diversity of content cached within the community.…”
Section: A Online Reactionary Approachmentioning
confidence: 99%
“…In fact, it is reported that IT downtime due to equipment failures costs enterprises billions of dollars a year [1]. In the area of information-centric networking (ICN), the authors in [6] investigated the provision of information resilience through a caching approach based on the concept of modularity.…”
Section: Introductionmentioning
confidence: 99%